A novel beam steerable antenna based on dual-reconfiguration technique. Issue 7 (3rd May 2017) - Cheng, You-Feng; Shao, Wei; Ding, Xiao; Yu, Mengxia; Ma, Jing; Jin, Congjun
Abstract: In this paper, a novel beam-steerable antenna based on a dual-reconfiguration technique is presented. The proposed antenna with a double-layer structure operates at 3.65 GHz. On the lower layer, a coplanar parasitic structure whose operational principle is similar to a quasi-Yagi strip structure is used as the driven element to supply the first-level reconfiguration. The parasitic upper layer which adopts a pixel surface is implemented for the second-level reconfiguration. By switching four PIN diodes on the lower layer and changing the pixel surface of the upper layer, the proposed antenna is capable of realizing beam steering ( θ  = 0°, ±10°, ±20°, ±30°, ±40°, ±50°, and ±60°) with a gain fluctuation lower than 1 dB. A multi-objective genetic algorithm and a co-simulation strategy are used to optimize the operating state of the pixel surface. The antenna is optimized, fabricated and measured. The measured results agree well with the simulated ones, and they validate the powerful reconfigurable ability of the proposed antenna.